Interações e relações de amizade: um estudo longitudinal no contexto de uma escola inclusiva - CASADO, Carla de Cássia Carvalho (Universidade Federal do Pará, 2018)
The present study has proposal to investigate longitudinally the friendship of students considered included in a public school, identified by the Education office of the state as a reference in educational inclusion. The school was located on the metropolitan area of Belém, Pará and the study took place during the years 2007 to 2009. Given the complexity of the relations of friendship, it was opted for a multiple case study involving four focal partners and their friends, colleagues, teachers and technicians. The approach of collection and analysis of data were structured through multiple methodological strategies. The research occurred in two phases, the first called preliminaries, which involved a pilot research, ethical procedure, choice of school, classes and focal participants, and a case study, which included a sociometric interview, semi-structured interviews, structured situations and participatory observation. The elements capable of quantification obtained in the sociometric interview were placed in "Excel" spreadsheets program, categorized and handled according to their specifications. The data obtained in the field journal and in the interviews have been transcribed to text-editing program "Word" and later organized in terms of thematic dimensions and categories of analysis according to the model of Hinde: reciprocity and complementarity, strength and power, intimacy, interpersonal perception, commitment and satisfaction. The data obtained in the case study indicated that two of the focal partners, one with Cerebral Palsy and the other with ADHD, were socially rejected throughout the study and did not obtain reciprocal friends. The student with mental disability has obtained only a friend throughout the research and remained alone when this friend was not present. The focal participant with hearing impairment experienced the collective friendship with three students during most of the research. By interviews the reason of rejection and social preferences were related to aspects such as, physical appearance, prejudice, cognitive, physics and communication difficulties, sharing of objects and experiences, among others. As regards to the relations of friendship, it was realized that the perception of the people who make up the school context made it difficult, but hasn't stopped the focal partners build reciprocal friendships. In the relations existed a positive perception of friend and they showed support and satisfaction in the relationship, they did not recognize the existence of problems between them and usually agreed with each other. Friends showed affection publicly and shared among themselves confidences and thoughts, in addition to identifying their preferences. Friends cared to serve the needs of each other and there was interest in maintaining the relationship. Some friendships lasted the three years of research, other had its end in 2008 when friends were transferred from school or changed to another class. Finally, it was possible to identify the existence of friendships among students with and without disabilities, and that these relations are characterized as satisfactory, filled with demonstrations of respect and affection, which can lead us to the understanding that friendship is an element of protection against discrimination and the difficulties experienced day by day, and people should invest in creating strategies that can stimulate the construction and maintenance of these relationships.